Autoionization widths by Stieltjes imaging applied to Lanczos pseudospectra - Kopelke, Sören; Gokhberg, Kirill; Cederbaum, Lorenz S.; Tarantelli, F.; Averbukh, V. (The journal of chemical physics, 2011)
Excited states of atoms and molecules lying above the ionization threshold can decay by electron emission in a process commonly known as autoionization. The autoionization widths can be calculated conveniently using Fano formalism and discretized atomic and molecular spectra by a standard procedure referred to as Stieltjes imaging. The Stieltjes imaging procedure requires the use of the full discretized spectrum of the final states of the autoionization, making its use for poly-atomic systems described by high-quality basis sets impractical. Following our previous work on photoionization cross-sections, here we show that also in the case of autoionization widths, the full diagonalization bottleneck can be overcome by the use of Lanczos pseudospectra. We test the proposed method by calculating the well-documented autoionization widths of inner-valence-excited neon and apply the new technique to autoionizing states of hydrofluoric acid and benzene.